Low academic achievement for sixth grade literary students in the schools of Babylon Governorate In general exams from the point of view of teachers (Journal of the College of Basic Education, 2022)
the teachers' point of view To achieve the goal of the research, the researcher prepared a questionnaire. consisting of (62) items to identify the reasons for low achievement, each of which represents one of the possible causes of low achievement. Its validity and reliability were verified; The researcher used the descriptive approach in the research. The study sample consisted of (310) teachers and schools, which is approximately (10%) of the total community.